Relationship between the percentage of predicted cardiorespiratory fitness and cardiovascular disease risk factors in pre-menopausal women: A Monet study - Abdulnour, Joseph (University of Ottawa (Canada), 2009)
Objective. To determine the relationships between the percentage predicted cardiorespiratory fitness (%CRF) and the anthropometric and metabolic cardiovascular disease risk factors in asymptomatic pre-menopausal women. Methods. Data are baseline values obtained in 97 pre-menopausal women (age: 49.9+/-1.9yrs; BMI: 23.2+/-2.2kg/m2) participating in a longitudinal study. Outcome measures: VO2 peak, body mass index (BMI), body composition [%fat, fat mass (FM), fat-free mass (FFM)], waist circumference (WC), abdominal subcutaneous adipose tissue (ScAT), visceral AT (VAT), resting blood pressure, fasting lipids, glucose and insulin levels. Results. %CRF was significantly associated with BMI, FM, %fat, WC, ScAT, VAT, triglycerides, triglycerides/HDL-C, total cholesterol, total cholesterol/HDL-C and fasting insulin levels (-0.59>r<0.31; 0.01>P<0.05). The stepwise multiple regression analysis showed that %CRF was only independently correlated with plasma triglyceride levels. Conclusion. The results suggest that %CRF was not a major predictor of anthropometric and metabolic variables associated with an increased risk of cardiovascular disease in women. Finally, the use of the %CRF over VO2 peak needs further studies. Keywords. cardiorespiratory fitness, cardiovascular disease, body composition, metabolic profile, pre-menopausal women.
Keywords: Health Sciences, Recreation.